The need for independent advocacy for people subject to mental health community treatment orders. (September 2019) - Weller, Penelope; Alvarez-Vasquez, Susan; Dale, Matthew; Hill, Nicholas; Johnson, Brendan; Martin, Jennifer; Maylea, Chris; Thomas, Stuart
Abstract: Independent mental health advocacy (IMHA) has been proposed as a way of maintaining peoples' rights in involuntary settings, but little is known about the challenges and opportunities associated with the provision of independent mental health advocacy to those on compulsory treatment orders in the community. In Victoria, Australia, an IMHA service is available to people who are at risk of or subject to compulsory treatment, including those who are subject to Community Treatment Orders. The IMHA service is based on the independent advocacy model developed in the United Kingdom. This paper details the benefits and challenges of providing independent non-legal advocacy to those in the community, drawing on a 15-month independent co-produced evaluation of the IMHA service. With limited publicly available sector level data, the evaluation employed qualitative approaches. Issues raised include the need to better target limited resources in the most effective way and the problem of ensuring timely and adequate access. While advocacy was well received by consumers, tensions specific to the community setting were influenced by the attitudes of clinicians to need, risk and recovery as opposed to a coherent understanding of consumer preference and choice.